A Case of Pregnant Uterus Perforation During Laparoscopy - S. V. Shramko; O. A. Volkov (Неотложная медицинская помощь, 2023)
RELEVANCE Pregnant uterus perforation during laparoscopy is a rare complication, accompanied by a higher risk of infection and miscarriage. Clinical management of pregnancy and its outcome have practical interest and need discussion.AIM To provide a clinical case of pregnant uterus perforation during laparoscopy.MATERIAL AND METHODS  Patient L., 34 years old, with a tumor of the right ovary and 21–22 weeks of pregnancy. Result The article describes a clinical case of independent childbirth on time after pregnant uterus perforation during laparoscopy with removing a significant volume of amniotic fluid in a 21–22 weeks pregnant woman.CONCLUSION The prolongation of pregnancy and independent childbirth on time after uterus perforation with a gestation period of 21 or 22 weeks is possible in case of timely diagnosis of the complication, careful restoration of uterine integrity and rational management of the postoperative period.